Cyprus : Third Post-Program Monitoring Discussions-Press Release and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper presents the Third Post-Program Monitoring discussions with Cyprus. Cyprus's rapid recovery is expected to slow gradually; however, the outlook remains favorable. Economic growth is gradually decelerating but remains strong, buoyed by the services and construction sectors, partly financed with foreign direct investment. While employment is picking up, wage pressures and inflation remain low. A large fiscal surplus is helping to lower public debt after a sizable one-off increase related to the sale of Cyprus Cooperative Bank in the year 2018. Repayment capacity appears to be adequate under the baseline scenario given the expected decline of gross public debt, a stable debt servicing profile, and continued favorable market conditions. Policies should aim to continue strengthening bank balance sheets while avoiding the commitment of public resources. The Estia scheme, aimed at encouraging non-performing borrowers to start servicing their loans, should not be allowed to lead to further risks of moral hazard. The subsidy support, mandated write-offs by banks and enhanced foreclosure threats on re-defaulting restructured loans are expected to strengthen incentives to service restructured loans.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet